2015
DOI: 10.3390/agriculture5040991
|View full text |Cite
|
Sign up to set email alerts
|

Removing Gaseous NH3 Using Biochar as an Adsorbent

Abstract: Ammonia is a major fugitive gas emitted from livestock operations and fertilization production. This study tested the potential of various biochars in removing gaseous ammonia via adsorption processes. Gaseous ammonia adsorption capacities of various biochars made from wood shaving and chicken litter with different thermal conditions and activation techniques were determined using laboratory adsorption column tests. Ammonia adsorption capacities of non-activated biochars ranged from 0.15 to 5.09 mg·N/g, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…This resulted in three kinetic constants for the Arrhenius equation at constant T (E a 1 = 141 kJ mol −1 , A 1 = 1.89 × 10 14 h −1 ; E a 2 = 75.0 kJ mol −1 , A 2 = 1.15 × 10 7 (1.59) kg −0.52 h −1 ; and, E a 3 = 74.3 kJ mol −1 , A 3 = 1.89 × 10 7 h −1 ). In addition to modelling the HTC kinetics in terms of the three basic biomass components (i.e., hemicellulose, cellulose, and lignin), it will be useful, especially for combustion applications of HC, if the proximate components (i.e., volatile matter, fixed carbon, and ash contents) of the feedstock and HC can be predicted with simple kinetic models, as done by Ro et al [13] for pyrolyzing animal manures. The proximate components of combustion fuels are commonly used to characterize fuel sources by power industry.…”
Section: Basic Kinetic Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This resulted in three kinetic constants for the Arrhenius equation at constant T (E a 1 = 141 kJ mol −1 , A 1 = 1.89 × 10 14 h −1 ; E a 2 = 75.0 kJ mol −1 , A 2 = 1.15 × 10 7 (1.59) kg −0.52 h −1 ; and, E a 3 = 74.3 kJ mol −1 , A 3 = 1.89 × 10 7 h −1 ). In addition to modelling the HTC kinetics in terms of the three basic biomass components (i.e., hemicellulose, cellulose, and lignin), it will be useful, especially for combustion applications of HC, if the proximate components (i.e., volatile matter, fixed carbon, and ash contents) of the feedstock and HC can be predicted with simple kinetic models, as done by Ro et al [13] for pyrolyzing animal manures. The proximate components of combustion fuels are commonly used to characterize fuel sources by power industry.…”
Section: Basic Kinetic Modelsmentioning
confidence: 99%
“…13 C-NMR analysis of HC from glucose revealed that 60% of the carbon atoms are cross-linked furan-based structures directly via either sp 2 or sp 3 type carbon groups [92], in contrast to the higher degree of arene-like structures found in pyrolysis chars from the same substrate [93]. Further 13 C-NMR analyses of chars from livestock waste have shown that, while HCs have a larger degree of aromaticity than pyrochars made at the same temperature (~43-55% vs. 26-32%; 250 • C), the aromaticity of pyrochars increases with increasing production temperature, reaching over 90% (600 • C) [72].…”
Section: Surface and Bulk Properties Of Hcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ro et al [6] performed ammonia adsorption capacity experiments on various biochar samples, one of which was produced from wood shavings at a similar temperature (500 • C) to the biochar used in this study and was determined to have an ammonia adsorption capacity of 0.84 mg [NH 3 -N]·g biochar −1 . This reported ammonia adsorption capacity equates to the capacity of the biochar to adsorb only the amount of NH 3 emitted in~one day under the conditions studied for a biochar dose of 4.56·kg·m −2 , i.e., much shorter than observed to be effective in this research.…”
Section: Treatment Effects On Ammonia and Hydrogen Sulfidementioning
confidence: 99%
“…Biochar has a long history of being used as a soil amendment. Only recently has biochar been employed in wastewater and manure composting to absorb various compounds (Table 1) and it has been shown to adsorb NH 3 [5,6]. In these recent studies, biochar's ability to mitigate emissions from livestock has focused solely on the land application and composting of manures and on few target gases.…”
Section: Introductionmentioning
confidence: 99%